Individualized home training in head and neck cancer patients is safe and has positive short- and medium-term effects –results of a multicenter, single-arm intervention trial (OSHO #94) - Felser, Sabine; Bonke, Lars A.; Glass, Änne; Strüder, Daniel; Stolle, Jana; Schulze, Susann; Blaurock, Markus; Steinmetz, Anke; Daunheimer, Julia; Kriesen, Ursula; Grosse-Thie, Christina; Junghanss, Christian (Frontiers in Oncology, 2025)
IntroductionDespite targeted exercise interventions alleviating functional deficits in head and neck cancer (HNC) patients, many patients are insufficiently physically active. A promising approach to reducing barriers could be individually adaptable home training. The “OSHO #94” study examined the short-term effectiveness, the medium-term sustainability, and the safety of an individualized home exercise programMethodsThis multicenter, single-arm, interventional study included patients in aftercare or in stable remission. Participants were advised to perform an individualized home exercise program (mobilization, coordination, strengthening, and stretching) at least three times a week and moderate-intensity endurance training two to three times a week. During the 12-week intervention, they kept a training diary and received weekly physiotherapist calls. In the subsequent 12-week follow-up (FU), participants were asked to continue training. The evaluation of short-term effects (between pre- and post-intervention) and medium-term effects (incl. FU), included the assessment of quality of life (QoL), physical activity level (Leisure Score Index (LSI); weekly amount), body composition, shoulder/cervical spine range of motion, fall risk, and aerobic performance. Adverse events were recorded.ResultsFifty-three patients (57% male) were enrolled, 83% completed the post assessment, and 72% completed FU. During the intervention, participants exercised for 257 min/week (with 95 minutes individual and 162 minutes endurance). The pre-post intervention effect on the global QoL was small (rw=0.20, p=0.186). Moderate effects were found in emotional (rw=0.38, p=0.011) and social functioning (rw=0.46, p=0.002), fatigue (rw=0.37, p=0.013), and dyspnea (rw=0.32, p=0.035). LSI increased significantly (25 vs. 39, p=0.003), whereas total physical activity duration remained unchanged (280 vs. 290 min/week, p=0.160). Small effects were observed on body composition. The largest effects were seen in physical functioning, particularly aerobic performance (rw=0.67, p<0.001). Nine participants (17%) reported training-related adverse events, primarily pain. Half of participants (48%) continued with individual training during FU. Some short-term effects could be detected medium-term.DiscussionPhysical activity level improved despite an unchanged activity duration suggesting an increased training intensity. With individualized home exercises and remote support, home training was effective and safe. After support ended, patients maintained their activity level and the effects were sustained, suggesting suitability for routine care.